2006
DOI: 10.1007/s11172-006-0322-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of derivatives of a new heterocyclic system pyrazolo[3,4-b]pyrido[1′,2′: 1,2]imidazo[4,5-d]pyridine

Abstract: 1 [4 Aminoarylpyrazolo[3,4 b]pyridin 5 yl]pyridinium chlorides undergo cyclization un der reflux in tert butanol in the presence of an excess of potassium tert butoxide to form tetracyclic derivatives of pyrazolo[3,4 b]pyrido[1´,2´:1,2]imidazo[4,5 d]pyridine. The reac tion scheme of the processes is proposed. The structures of the reaction products were con firmed by physicochemical methods. Key words: 2 chloroacetamido 4 cyanopyrazole, 1 [4 aminopyrazolo[3,4 b]pyridin 5 yl]pyridinium chloride, pyrazolo[3,4 b]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…For example, in the pyrazole ring system C (4) is the most electron rich carbon, thus, H (4) in is expected to appear at higher field at δ 6.31 ppm. On the other hand, H (5) is linked to the carbon attached to nitrogen atom and thus it's deshielded to appear in the region δ 7.5 -8.5 ppm [26][27][28]. The 1 H NMR spectra of isolated reaction products revealed, in each case, a singlet signal at δ 8.5 ppm which indicates the presence of the pyrazole H (5) rather than H (4) in the structure of the isolated products.…”
Section: Resultsmentioning
confidence: 96%
“…For example, in the pyrazole ring system C (4) is the most electron rich carbon, thus, H (4) in is expected to appear at higher field at δ 6.31 ppm. On the other hand, H (5) is linked to the carbon attached to nitrogen atom and thus it's deshielded to appear in the region δ 7.5 -8.5 ppm [26][27][28]. The 1 H NMR spectra of isolated reaction products revealed, in each case, a singlet signal at δ 8.5 ppm which indicates the presence of the pyrazole H (5) rather than H (4) in the structure of the isolated products.…”
Section: Resultsmentioning
confidence: 96%
“…This assignment is based on the fact that in the pyrazole ring, H-4, is more shielded than H-5. Thus, the signal of H-5 usually appears at δ 8.66–8.69 [25], whereas that of H-4 appears at δ 5.81–5.89 [26,27]. The above-mentioned information indicated that the reaction of enaminone 1 with hydrazonoyl chloride 14 is regiospecific.…”
Section: Resultsmentioning
confidence: 99%
“…The latter reaction products were assumed to be formed via initial 1,3-dipolar cycloaddition of the nitrilimines 5a-m to the activated double bond in compound 3 to afford the non-isolable cycloadducts 6a-m which undergoes loss of dimethylamine yielding the final pyrazole derivatives 7a-m. [44][45][46] The 1 H NMR spectra of the isolated products 7a-m revealed, in each case a singlet signal in the region of 8.40-8.72 ppm which indicates the presence of the pyrazole H-5 rather than H-4. This conclusion was further confirmed chemically by the reaction compounds 7a,d,g with hydrazine hydrate, to afford pyrazolo[3,4-d]pyridazines 8a-c, respectively (Scheme 2).…”
Section: Methodsmentioning
confidence: 96%